2013
DOI: 10.1186/1477-7819-11-15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of manual lymphatic drainage on breast cancer-related lymphedema: a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundLymphedema is a common complication of axillary dissection for breast cancer. We investigated whether manual lymphatic drainage (MLD) could prevent or manage limb edema in women after breast-cancer surgery.MethodsWe performed a systematic review and meta-analysis of published randomized controlled trials (RCTs) to evaluate the effectiveness of MLD in the prevention and treatment of breast-cancer-related lymphedema. The PubMed, EMBASE, CINAHL, Physiotherapy Evidence Database (PEDro), SCOPUS, and Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
109
1
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 30 publications
6
109
1
12
Order By: Relevance
“…The most important component of CDT phase 1 treatment is short-stretch compression bandaging. Several studies showed that efficient and effective results could be obtained in mild and moderate lymphedema without MLD component (22,24,25). In our study, 14 patients were treated with phase 1 components including education, skin care, exercise, and daily multi-layer short-stretch compression bandaging.…”
Section: Discussionmentioning
confidence: 99%
“…The most important component of CDT phase 1 treatment is short-stretch compression bandaging. Several studies showed that efficient and effective results could be obtained in mild and moderate lymphedema without MLD component (22,24,25). In our study, 14 patients were treated with phase 1 components including education, skin care, exercise, and daily multi-layer short-stretch compression bandaging.…”
Section: Discussionmentioning
confidence: 99%
“…It manifests as a chronic edema, causing discomfort, loss of function, deformity and fatigue 3,4 . Psychological changes are also observed and negatively affect body image and self-esteem 5 .…”
Section: Introductionmentioning
confidence: 99%
“…The International Society of Lymphology 6,7 supports the use of CDT, which involves a two-stage treatment program: intensive and maintenance care. Intensive treatment allows a substantial reduction in the volume of lymphedema 3,14 and includes four components: manual lymphatic drainage, skin and nail care, compression bandaging and therapeutic exercises 15,16 . Considering CDT for the postoperative lymphedema treatment of breast cancer, there is a need to assess the evidence of this technique.…”
Section: Introductionmentioning
confidence: 99%
“…62 Conversely, a recent systematic review of the RCTs evaluating the effects of MLD on breast cancer-related secondary lymphedema indicates that MLD does not prevent or treat lymphedema. 63 However, there were clinical and statistical inconsistencies between the various studies, confounding the evaluation of the reviewed studies. 63 Compression therapy has been advocated for the management of lymphedema and in the management of high perfusion microangiopathy in patients with DFU.…”
Section: Decongestion Therapymentioning
confidence: 99%
“…63 However, there were clinical and statistical inconsistencies between the various studies, confounding the evaluation of the reviewed studies. 63 Compression therapy has been advocated for the management of lymphedema and in the management of high perfusion microangiopathy in patients with DFU. Compression therapy with elastic stockings reduces capillary leakage and formation of edema, and may retard the progression of diabetic microangiopathy.…”
Section: Decongestion Therapymentioning
confidence: 99%